Electroacupuncture alleviates ulcerative colitis by targeting CXCL1: evidence from the transcriptome and validation - Zhang, Rui-Bin; Dong, Long-Cong; Shen, Yuan; Li, Hong-Ying; Huang, Qin; Yu, Shu-Guang; Wu, Qiao-Feng (Frontiers in Immunology, 2023)
Background: We aimed to use transcriptomics, bioinformatics analysis, and core gene validation to identify the core gene and potential mechanisms for electroacupuncture (EA) treatment of ulcerative colitis (UC). Materials and Methods: EA was performed in mice after induction of UC via dextran sodium sulfate. Body weight, disease activity index (DAI), colon length, and hematoxylin-eosin of the colon tissue were used to evaluate the effects of EA. Mice transcriptome samples were analyzed to identify the core genes, and further verified with human transcriptome database; the ImmuCellAI database was used to analyze the relationship between the core gene and immune infiltrating cells (IICs); and immunofluorescence was used to verify the results. Results: EA could reduce DAI and histological colitis scores, increase bodyweight and colon length, and improve the expression of local and systemic proinflammatory factors in the serum and colon of UC mice. Eighteen co-differentially expressed genes were identified by joint bioinformatics analyses of mouse and human transcriptional data; Cxcl1 was the core gene. EA affected IICs by inhibiting Cxcl1 expression and regulated the polarization of macrophages by affecting the Th1 cytokine IFN-γ, inhibiting the expression of CXCL1. Conclusions: CXCL1 is the target of EA, which is associated with the underlying immune mechanism related to Th1 cytokine IFN-γ.